1970
DOI: 10.1002/oms.1210030706
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectra of selected beta‐carbolines [β‐9H‐pyrido(3,4‐b)indoles]

Abstract: The mass spectra of fifteen B-carbolines have been interpreted and proposed fragmentations have been substantiated by means of deuterium-labeling and accurate mass determinations. Most decompositions were predictable. An interesting fragmentation was observed in the spectra of 1 -alkyl-l,2,3,4-tetrahydro-~-carbolines, which rearrange to expel an alkylamino (RNH) radical from the molecular ion. 157 230-20 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 4 publications
3
5
0
1
Order By: Relevance
“…A cleavage of a methyl radical however, was observed to a minor extent also, leading to the formation of m/z 199 (3, 12%) and m/z 213 (5, 17%), respectively. The observation of alkyl-cleavages was consistent with Coutts et al [33] and Gynther [31] who reported on the EI mass spectra of several 1-monosubstituted-THBCs. 1-Ethyl-monosubstituted-THBCs have also been reported to show a dominating C 2 H 5 radical cleavage [34].…”
Section: Ei-it-ms Of the Open Chain Analogues (Summarised Insupporting
confidence: 90%
“…A cleavage of a methyl radical however, was observed to a minor extent also, leading to the formation of m/z 199 (3, 12%) and m/z 213 (5, 17%), respectively. The observation of alkyl-cleavages was consistent with Coutts et al [33] and Gynther [31] who reported on the EI mass spectra of several 1-monosubstituted-THBCs. 1-Ethyl-monosubstituted-THBCs have also been reported to show a dominating C 2 H 5 radical cleavage [34].…”
Section: Ei-it-ms Of the Open Chain Analogues (Summarised Insupporting
confidence: 90%
“…After the expulsion of the nitro subtituent the main fragmentation path of 1a, 1b, 2a, 2b, 3a, 3b, 5a and 5b are Sep-Oct 2001Vol. 38 (8) 62 (2) similar to those described for the corresponding β-carboline [12,62]. Finally, although very clear ei-ms spectra have been reported for dinitroaromatic compounds, e.g., dinitrocarbazoles [61], (see in Table 3 ei-ms data for 1,6-dinitro and 3,6-dinitrocarbazole, compounds 6c and 6d, respectivley), peaks of very low intensity were obtained from the dinitro derivatives of harmine (Table 3, compound 3c) by ei-ms even at very soft experimental conditions (low temperature at the injection chamber; low voltage for the ionizing electron source).…”
Section: Nitro-β-carbolines Obtained By Nitration Of Commercial β-Carsupporting
confidence: 58%
“…If this was the case, the dominating mechanism, i.e. base peak formation, would then be represented by alkyl cleavages [20][21][22][23]. CI-MS-MS confirmed the [M + H] + to occur at m/z 187 with further dissociation to m/z 144.…”
Section: Gc-ms Analysis Of N-chloromethyl-dmt Chloridementioning
confidence: 99%
“…2(C1 and C2), respectively. Under EI conditions, a characteristic base peak at m/z 143 was observed which is known to occur after retro-Diels-Alder fragmentation (RDA) [20]. The presence of this base peak ion can also provide some structural information because it points towards the absence of any substituent at position C-1.…”
Section: Gc-ms Analysis Of N-chloromethyl-dmt Chloridementioning
confidence: 99%